PENERAPAN MODEL COOPERATIVE LEARNING TIPE THINK PAIR SHARE UNTUK MENINGKATAN AKTIVITAS DAN HASIL BELAJAR MATEMATIKA SISWA KELAS VI SD NEGERI KALIWADAS 01 - Paryanti, Paryanti (UNIVERSITAS MUHAMMADIYAH METRO, 2015)
The aims of this research were to increase the activities and the result of study by implementation of cooperative learning model type think pair share. The method of the research was Classroom Action Reserach. The instrument of data collection used observation sheet and test. Technique of data analysis used qualitative and quantitative analysis. The result showed that the student activity in cycle I 62,54% (active) and cycle II 78,27%(active). The result study of the cognitivie in cycle I 71,70% (good) and cycle II 78,61% (good).Â Keywords : Â activity, result study, think pair share